Data sources and ingestion big data layers: meta-modeling of key concepts and features - Erraissi, Allae; Belangour, Abdessamad (International Journal of Engineering and Technology, 2018)
A deluge of data is to be expected in the years to come. Nowadays, huge masses of data is produced every day. For example, if we take only social network users and the Internet of Things, we shall find that they generate large volumes of varied data that have to be transmitted, recorded and processed at high speed. These data are an important source of information that can improve the performance of predictions. Hence, the data are no longer in net structures, easy to consume, but they are represented in different types of structures, namely structured, semi-structured and unstructured data. At the Big Data architecture level, these different data sources are located in the Data Sources layer, which is the starting point for any further processing of Big Data. Indeed, this layer has a direct relationship with the Ingestion layer, which is in charge of validating, transforming, cleaning, reducing and integrating data that can be used later on by the Hadoop ecosystem. In this paper, we applied techniques related to Model Driven Engineering "MDE" to propose a universal Meta-modeling for both Data Sources and Ingestion Big Data layers. These meta-models are platform independent according to Model Driven Architecture pattern, which describes the structures of Data Sources and Ingestion independently from any specific platform.